PENGARUH KOMPETENSI DAN DISIPLIN KERJA TERHADAP KINERJA GURU DIMEDIASI KOMITMEN ORGANISASIONAL (Studi Kasus Pada Guru PNS SD Di Kecamatan Sulang Kabupaten Rembang) (Jurnal Mahasiswa Pasca Sarjana, 2015)
The main problem of researchare how effect of competence and dicipline on teacher performance with organizational commitment variabel intervening. The population in this study is the elementary teachers, in Sulang Rembang many as 122 respondent. Data were collected using a questionnaire, after which the data were processed using SPSS 17. Result of research analysis express that (1) competence gives positive influence and significant toorganizational commitment, (2) dicipline gives positive influence and significant to organizational commitment, (3) competence gives positive influence and significant to teacher performance, (4) dicipline gives positive influence and significant to teacher performance, (5) organizational commitment gives positive influence and significant to teacher performance, (6)organizational commitment isn”t variabel interveningcompetenceto teacher performance, (7)organizational commitment isn”t variabel intervening disipline to teacher performance.Keywords: Competence, Dicipline, Organizational Commitment, Teacher Performance